Caracterização das Atividades Experimentais nos Livros Didáticos de Ciências da Natureza e suas Tecnologias: um olhar para a Coleção ser Protagonista do PNLD 2021 - Pimentel, Thalia Marques (Universidade Federal do Tocantins, 2024)
In Brazil, the National Textbook Program (PNLD) is responsible for selecting and distributing textbooks to public schools. In 2021, the Ser Protagonista collection by SM Educação was one of the options offered by PNLD for the area of Natural Sciences and its Technologies. The present study is a qualitative research using an exploratory approach with an investigative purpose that aims to describe the experimental practices and characterize them according to the selected criteria, in the textbooks of Natural Sciences and their technologies from the collection being protagonist of the publisher SM education, focusing on teaching Chemistry. The National Book and Didactic Material Program (PNLD) 2021 brought changes in the organization of high school textbooks. The changes are directly related to meeting the demands of the BNCC and the reorganization of the curricula of the Public Basic Education Network to meet the Secondary Education Reform, the New Secondary Education (NEM) that took place in 2017, which introduced a new curriculum and the order of the curricular components. These experiments play a crucial role in teaching Chemistry, bringing with it a variety of benefits and importance for students' learning in this discipline. They offer a practical and interactive approach, allowing students to directly engage with chemical concepts and principles, which results in more meaningful learning.